Incidence of cleft lip and palate in Tehran - Jamilian A; Nayeri F; Babayan A (Wolters Kluwer Medknow Publications, 2007)
The purpose of this study was to assess the epidemiology and some of the possible risk factors causing oral cleft in Tehran. The study was a 7-year retrospective study from March 1998 to March 2005. Twenty-five live births with cleft lip and/or palate (CL ± P) were born between 20 March 1998 and 20 March 2005 from the total of 11,651 live births in a maternity hospital in Tehran. After recognizing the child as a cleft patient, previous and following children born were recognized as a noncleft sample. Cleft and noncleft samples were compared for variables such as gender, mother′s age, parity, consanguineous marriage and infant′s weight, and then analyzed with Chi-square. The overall incidence was 2.14 per 1000 live births. CL+ P is more prevalent, which was 52% and the least incidence was for "only cleft lip′′ patients, which was 12%. This study reveals that the incidence of oral clefts in Tehran is higher than many other countries. Consanguineous marriage and low birth weight in cleft group were significant statistically from those of noncleft group.